PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL ADAPTIF PADA TEMA KESEHATAN PENCERNAAN TERHADAP KOMPETENSI IPA SISWA KELAS VIII SMPN 8 PADANG - Tri Septiani; Zulhendri Kamus; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2018)
The science teaching in the 2013 curriculum should be implemented by integrating teaching material and literacy skill. The real conditions at school show that science teachers have difficulty to integrate among teaching materials of Physics, Biology and Chemistry. Besides that, integrated teaching material in integrated science textbooks and integration literacy in science teaching were low. A solution of this problem was to apply the adaptive contextual teaching model on grade VIII  students in SMPN 8 Padang. The type of this research was quasi experimental with randomized control-group only design. The population of this research was students of grade VIII in SMPN 8 Padang, while the samples of this research were taken by using purposive sampling technique. Experiment group in this research was grade VIII B students, while control group was grade VIII H students. The instruments of this research were observation assessment for attitude competence, written test for knowledge competence and performance appraisal for skills competence. The data which obtained were analyzed by descriptive statistics and two compare means test. The result of the analysis shows that the application of adaptive contextual learning model gives a significant effect on the attitude, knowledge and skill competency of the grade VIII students in SMPN 8 Padang at 95% confident level.